Return to Recreational Sport Following Lumbar Fusion. Issue 4 (May 2020) - Jain, Nickul S.; Lin, Charles C.; Halim, Alexander; Knight, Brian; Byrne, Connor T.; Alluri, Ram; Bhatia, Nitin N.; Lee, Yu-Po
Abstract : Study Design: This was a retrospective questionnaire study at a single academic medical center. Objective: The objective of this study was to obtain information on rates of return to sport following lumbar fusion as well as sport-specific effects to improve evidence-based preoperative patient counseling. Summary of Background Data: Lumbar spinal fusion is one of the fastest-growing surgical procedures, with the majority being in patients aged 60 years and older. Remaining active is an important consideration for elderly patients undergoing lumbar spinal fusion. Golf, swimming, and biking are common forms of recreational exercise for an older population in whom lumbar fusion is often performed. There is a lack of data in the current literature regarding rates of return to recreational sporting activities following elective lumbar fusion. Methods: Following Institutional Review Board approval, all patients undergoing lumbar fusion at a single institution from 2012 to 2016 were screened and included in this study. A minimum of 1-year postoperative follow-up was required. A total of 117 patients were identified undergoing single-level or multilevel lumbar fusion during this time period. The average age was 63 years. Questionnaires were obtained to screen and identify patients who participated in 1 of 3 recreational sports before surgery (golf, swimming, and biking). Preoperative and postoperative collected outcome measures were then compared using the Student t test. Results: Of the 117 identified lumbar fusion patients, 32 patients (27%) participated in 1 of the 3 most common recreational sporting activities of golf, swimming, or biking. Within the golf cohort (n=13), 100% of patients returned to recreational golfing postoperatively. There was a statistically significant reduction in Visual Analog Scale (VAS) pain scores postoperatively (6.3±3.7–1.8±2.4, P =0.01). Driving distance was reduced postoperatively (223.3±42.7–212.1±44.4 yards, P =0.042) and handicaps increased (12.8±8.4–17.0±11.4, P =0.02). Within the swimming cohort (n=9), 100% of patients returned to recreational swimming following lumbar fusion. There was a statistically significant reduction in VAS pain scores postoperatively (9.1±1.7–2.2±2.3, P =0.01). There was a trend towards increased amounts of swimming (times per week) postoperatively, however, this was not statistically significant (2.1±1.7–3.7±1.5, P =0.10). Within the biking cohort (n=10), 100% of patients returned to recreational biking following lumbar fusion. There was a statistically significant reduction in VAS pain scores postoperatively (6.7±4.0–1.3±1.7, P =0.03). There was a trend towards increased amounts of biking (times per week) postoperatively, however, this was not statistically significant (2.5±1.8–3.7±1.6 postoperatively, P =0.20). Conclusions: In the cohort of patients from this study who partook in golfing, swimming or bicycling, 100% were able to return to their respective sport by 3–9 months postoperatively and all had a significant reduction in pain. With regards to golfers, lumbar fusion likely has an adverse effect on their golfing ability with an increase in handicap and an expected reduction in driving distance.